Safety, tolerability, and pharmacokinetics of faldaprevir after single increasing doses in healthy subjects - Yong, Chan-Loi; Sennewald, Regina; Nehmiz, Gerhard; Quinson, Anne-Marie; Huang, Fenglei (Frontiers in Pharmacology, 2025)
Faldaprevir (FDV) is a novel NS3/NS4A inhibitor used in the treatment of hepatitis C infection in an interferon-free regimen. This study evaluated the safety, tolerability, and pharmacokinetics of FDV following a single dose in healthy male subjects and assessed the effect of food on FDV bioavailability. In the placebo-controlled, randomized, single-blind, single-increasing-dose part of the study (Part 1), 64 healthy male subjects were randomized to receive FDV in PEG/TRIS/meglumine solution at one of eight dose levels (4–1,200 mg, n = 6 per dose group) or placebo (n = 2 per dose group). In Part 2, the effect of food on the relative bioavailability (rBA) of 480 mg FDV in solution was evaluated in an open-label, crossover comparison, with and without a high-fat breakfast, in an additional 10 subjects (8 FDV and 2 placebo). Following single doses of 4–1,200 mg FDV, geometric mean (gMean) Cmax and AUC0-inf were 3.57–16500 ng/mL and 254–402000 h*ng/mL, respectively, displaying more than dose-proportional increases in exposure. FDV was slowly absorbed, with gMean t1/2 and median tmax of 15.5–39.2 h and 4.0–14.0 h, respectively; both were dose dependent. The urinary excretion of FDV was less than 0.1% of the dose. A high-fat breakfast increased systemic exposure to FDV in solution by 14%. FDV was generally well tolerated; subjects who experienced adverse events (AEs) recovered without sequelae, and no serious AEs were reported. Indirect (unconjugated) bilirubin of >3.0 mg/dL was observed in two subjects at 480 mg and five subjects at 1,200 mg. In conclusion, at single doses of 4–1,200 mg in healthy male subjects, FDV showed dose-dependent pharmacokinetics and was generally considered safe and well tolerated. Food had no clinically relevant effect on the rBA of FDV.